Implementation of Lean Hospital Intervention in Outpatient Pharmacy Depot at the National Brain Center Hospital Prof. Dr. dr. Mahar Marjono Jakarta, Indonesia - Dharmaningsih, Dwi; Andriani, Helen; Bashabih, Masyitoh; Tahir, Hadijah (Unnes Journal of Public Health, 2024)
Waiting time for prescription services indicates the quality of hospital services. The waiting time at the National Brain Center Hospital Prof. Dr. dr. Mahar Marjono Jakarta (RSPON Jakarta) Regular Outpatient Pharmacy Depot has not yet reached the standard of ≤30 minutes for non-concoction prescription, ≤60 minutes for concoctions prescription. This research aims to reduce the waiting time for outpatient prescription services using the Lean Hospital approach, which uses operational research methods with a qualitative approach through direct observation, interviews, and document review. In current state conditions, the lead time for non-concoction prescriptions is 46.7 minutes, with the ratio of value-added activity to total service time 25%:75%, while for concoctions prescriptions is 98.9 minutes, with the ratio of 27%:73%. The highest waste is waiting and overprocessing. Causes of waste are human resources inefficiency, simultaneous doctors' practice schedules, no separate system for regular and executive outpatient staff, e-prescriptions optimation, internet instability, and patient interruptions. Lean hospital intervention was the Balancing-Heijunka through modification of shifts and 5S. Future state results showed a 28% reduction in lead time for non-concoction prescriptions (33.3 minutes), while concoction prescriptions decreased by 32% (67.1 minutes). Lean Hospital can reduce waste and lead time for prescription services.